Deletion of macrophage migration inhibitory factor inhibits murine oral carcinogenesis: Potential role for chronic pro‐inflammatory immune mediators. Issue 6 (16th June 2016) - Oghumu, Steve; Knobloch, Thomas J.; Terrazas, Cesar; Varikuti, Sanjay; Ahn‐Jarvis, Jennifer; Bollinger, Claire E.; Iwenofu, Hans; Weghorst, Christopher M.; Satoskar, Abhay R.
Abstract : Oral cancer kills about 1 person every hour each day in the United States and is the sixth most prevalent cancer worldwide. The pro‐inflammatory cytokine 'macrophage migration inhibitory factor' (MIF) has been shown to be expressed in oral cancer patients, yet its precise role in oral carcinogenesis is not clear. In this study, we examined the impact of global Mif deletion on the cellular and molecular process occurring during oral carcinogenesis using a well‐established mouse model of oral cancer with the carcinogen 4‐nitroquinoline‐1‐oxide (4NQO). C57BL/6 Wild‐type (WT) and Mif knock‐out mice were administered with 4NQO in drinking water for 16 weeks, then regular drinking water for 8 weeks. Mif knock‐out mice displayed fewer oral tumor incidence and multiplicity, accompanied by a significant reduction in the expression of pro‐inflammatory cytokines Il ‐1β, Tnf ‐α, chemokines Cxcl1, Cxcl6 and Ccl3 and other molecular biomarkers of oral carcinogenesis Mmp1 and Ptgs2 . Further, systemic accumulation of myeloid‐derived tumor promoting immune cells was inhibited in Mif knock‐out mice. Our results demonstrate that genetic Mif deletion reduces the incidence and severity of oral carcinogenesis, by inhibiting the expression of chronic pro‐inflammatory immune mediators. Thus, targeting MIF is a promising strategy for the prevention or therapy of oral cancer. Abstract : What's new? Oral cancer patients often show increased levels of a cytokine called MIF. However, the precise role of this pro‐inflammatory cytokine in carcinogenesis is not completely understood. In this study, the authors examined the contribution of MIF to oral carcinogenesis by deleting the gene coding for MIF in a mouse model of oral cancer. Their findings indicate that loss of MIF reduces both the incidence and progression of oral tumors, and is also associated with reduced levels of inflammatory and cancer biomarkers. MIF may therefore be a potentially useful therapeutic target.